2020
DOI: 10.33021/jie.v5i1.1270
|View full text |Cite
|
Sign up to set email alerts
|

Study of Rainwater Harvesting Implementation

Abstract: In recent years, because of the changes in the environment and an increase in the global population, there is an increase in the threat of water scarcity. Therefore, there a need for developing water supply systems that is sustainable and resilient. Rainwater harvesting (RWH) systems are a decentralized sustainable water supply system that has the potential to be implemented. Industries, as one of the sectors that will be affected, could potentially gain many benefits through the implementation of RWH systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Michelle N Gunawan and Yunita Ismail in the journal Study of Rainwater Harvesting Implementation concluded that the Rainwater Harvesting (RWH) System is a possible solution to overcome the worrying problem of water scarcity [15]. Awawdeh M., Al-Shraideh S., Al-Qudah K. and Jaradat R. in the journal Rainwater harvesting assessment for a small size urban area in Jordan proves that large potential for exploited rainwater harvesting from rooftops and open areas is possible at Yarmouk University.…”
Section: Previous Researchmentioning
confidence: 99%
“…Michelle N Gunawan and Yunita Ismail in the journal Study of Rainwater Harvesting Implementation concluded that the Rainwater Harvesting (RWH) System is a possible solution to overcome the worrying problem of water scarcity [15]. Awawdeh M., Al-Shraideh S., Al-Qudah K. and Jaradat R. in the journal Rainwater harvesting assessment for a small size urban area in Jordan proves that large potential for exploited rainwater harvesting from rooftops and open areas is possible at Yarmouk University.…”
Section: Previous Researchmentioning
confidence: 99%